Peningkatan Literasi Kesehatan Masyarakat tentang Leukemia: Menguak Fakta dan Harapan Baru melalui Seminar Awam - Sasmithae, Lia; Didin Retno Indah Palupi; Sanggap Indra Sitompul (Jurnal Pengabdian Kampus, 2025)
The community service activity, conducted in the form of a public seminar titled "Not Just Blood Cancer: Unveiling Facts and New Hope in Leukemia Treatment," was successfully held in Palangka Raya. The seminar aimed to increase public awareness and knowledge regarding leukemia, a condition often misunderstood as simply a blood cancer. The event covered a comprehensive range of topics, including the definition of leukemia, its symptoms, diagnostic methods, and the latest advancements in treatment, with a particular focus on the role of bone marrow transplantation. A total of 60 participants attended the seminar, displaying significant enthusiasm and engagement throughout the session. The seminar was designed to be informative and accessible, ensuring that individuals from diverse backgrounds could grasp the complexities of the disease and the latest therapeutic developments. In addition to raising awareness, the event aimed to educate the public on the importance of early detection and the impact that timely interventions can have on patient outcomes.To assess the effectiveness of the seminar, an evaluation was conducted using pre-test and post-test methods. The results demonstrated a notable increase in participants' understanding of leukemia, indicating that the seminar successfully achieved its educational objectives. The pre-test and post-test data revealed a significant improvement in participants' ability to identify the symptoms of leukemia, understand the diagnostic procedures, and recognize the significance of emerging therapies, such as bone marrow transplantation.The findings of this community service initiative underline the effectiveness of public seminars as a tool for health education. By offering a platform for disseminating knowledge about leukemia and its treatments, the seminar not only contributed to early detection efforts but also played a vital role in improving the quality of life for leukemia patients. This activity highlights the importance of community-based educational interventions in fostering greater health literacy and promoting proactive healthcare behavior.